Patrones de comportamiento diurnos y estacionales de Tursiops truncatus y Stenella attenuata (Mammalia: Delphinidae) en el Golfo Dulce, Costa Rica - Cubero Prado, Priscilla (1998)
From July 1996 to June 1997, 123 sightings of bottlenose dolphins and 17 sightings of spotted dolphins were made in Golfo Dulce. south Pacific of Costa Rica. Behavioral patterns of both bottlenose and spotted dolphins were analyzed. classifying behavior in five categories such as travelling. feeding. passive socializing. active socializing and milling. Instantaneous data recording was used, and only sightings equal or longer than 15 minutes were considered. Correspondence Analysis revealed differences in diurnal patterns between the two species while seasonal patterns showed important similarities. Diurnal differences were explained in terms of external aspects (i.e. prey) instead of internal requirements due to time proportions for each activity were similar. Coincidence of time proportion spent on feeding activities during dry season (January-April) as well as coincidence of time proportion invested on active social activities during late wet season (September-December) in the two species were explained on a survival basis.